Energia solar fotovoltaica conectada à rede de energia elétrica em Cuiabá : estudo de caso - Apolônio, Daniel Moussalem (2014)
The increasing usage of solar photovoltaic systems because of the growth of economic competitiveness demands studies in applications and technological or process innovations in this field of knowledge. The evolution of the application of solar generation by the pioneers countries demonstrate the possibility of large investments in the sector in a near future, especially after the possibility of grid connection and distributed generation regulated by ANEEL in Brazil. The objective of this work is to study on-grid solar photovoltaic systems regarding its project, operation, power quality, system efficiency and the amount of energy generated, obtained by simulations and measurements, through a case study of an installed system working at the Federal University of Mato Grosso (UFMT), Cuiabá campus. The 510 Wp system generated 583,66 kWh of electric energy during a year of measurements and presented performance ratio of 0,657 in comparison to the 0,731 standard for PV systems of NREL (2005). Some system technical characteristics were checked and compared with nominal values on the manual. The results obtained by the softwares are appropriated as an assistant for projecting, energy generation prediction e financial feasibility for the incoming systems. The payback for the installed system is predicted to approximately 20 years and for 3 kWp systems in which the generation is used in the building before injected with B energy fee the viability is going to be reached in 2016. The payback of the investment on on-grid photovoltaic systems vary from each system, and tend to be susceptible to harsh variations, mainly due to legislations and government support and changes in the photovoltaics equipment prices and the electric energy rates.